2005
DOI: 10.1056/nejmoa043252
|View full text |Cite|
|
Sign up to set email alerts
|

Methicillin-ResistantStaphylococcus aureusDisease in Three Communities

Abstract: Community-associated MRSA infections are now a common and serious problem. These infections usually involve the skin, especially among children, and hospitalization is common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

48
851
16
18

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,367 publications
(933 citation statements)
references
References 33 publications
48
851
16
18
Order By: Relevance
“…Our intervention was in response to steadily increasing nosocomial infection rates over the previous few years and our rates may have increased more dramatically without this intervention. This increase is also consistent with national trends toward greater numbers of MRSA and VRE infections -including the recent emergence of a new strain of community-acquired MRSA [18].…”
Section: Discussionsupporting
confidence: 77%
“…Our intervention was in response to steadily increasing nosocomial infection rates over the previous few years and our rates may have increased more dramatically without this intervention. This increase is also consistent with national trends toward greater numbers of MRSA and VRE infections -including the recent emergence of a new strain of community-acquired MRSA [18].…”
Section: Discussionsupporting
confidence: 77%
“…Antimicrobial-resistant pathogens, especially methicillin-resistant S. aureus (MRSA), are increasingly isolated in nosocomial infections [17][18][19][20]. Several recent reports identified MRSA as the leading pathogen in SSTIs [21][22][23][24]; it also causes 20% to 50% of diabetes-associated foot infections in several countries and is associated with worse outcomes than other pathogens [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…While CA-MRSA can cause severe invasive infections, it predominantly causes SSTAs in young, otherwise healthy individuals. 2,3 Between 1997 and 2005, outpatient visits in the United States for skin and soft tissue infections rose by 50% and more than doubled at emergency departments (EDs). 4 In 2008, CA-MRSA accounted for 59% of all culturable skin and soft tissue infections in the U.S. EDs, 85% of which were abscesses.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,[7][8] Although most RCTs demonstrate no benefit, a few show a trend toward benefit, 7,11 and some authors have argued that these studies were underpowered to show a benefit that likely exists. 9 A 2007 systematic review and 2013 meta-analysis found no benefit from adjunctive antibiotics.…”
Section: Introductionmentioning
confidence: 99%